Analisis Pengembangan Manajemen Organisasi Pada Umkm Dapur Mama Iceng (Dmi) Desa Ngepoh - Taufikurrahman Taufikurrahman; Akhmad Qhusoyyi Shobri; Della Atanti; Ria Mei Yustiana; Ririn Aprilia Dewanti; Rizka Salma Nabila (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Strengthening micro, small and medium enterprises has great strategic importance, because they have the potentials to contribute to community economic activities, such as becoming the main source of income to improve the welfare of the majority of the people. MSME expertise is important because it increases MSME productivity and efficiency. In applying the MSME management model, it is necessary to carry out a Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis of daily operations related to business aspects, so that MSMEs know the development of their business in general. and appreciate it.